2016
DOI: 10.1186/s13068-016-0672-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of Holtermanniella wattica, Leucosporidium creatinivorum, Naganishia adeliensis, Solicoccozyma aeria, and Solicoccozyma terricola for their lipogenic aptitude from different carbon sources

Abstract: BackgroundThe ability of some microorganisms to accumulate lipids is well known; however, only recently the number of studies on microbial lipid biosynthesis for obtaining oleochemical products, namely biofuels and some building blocks for chemistry, is rapidly and spectacularly increased. Since 1990s, some oleaginous yeasts were studied for their ability to accumulate lipids up to 60–70% of their dry weight. Due to the vast array of engineering techniques currently available, the recombinant DNA technology wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 50 publications
3
19
0
2
Order By: Relevance
“…3b). Holtermanniella is a small, cold-tolerant genus of potentially parasitic fungi (38) that includes species able to metabolize diverse carbon compounds and generate unique fatty acid profiles (39).…”
Section: Discussionmentioning
confidence: 99%
“…3b). Holtermanniella is a small, cold-tolerant genus of potentially parasitic fungi (38) that includes species able to metabolize diverse carbon compounds and generate unique fatty acid profiles (39).…”
Section: Discussionmentioning
confidence: 99%
“…Leucosporidium creatinivorum DBVPG 4794, Naganishia adeliensis DBVPG 5195 and Solicoccozyma terricola DBVPG 5870 were used. They were previously selected on the basis of their superior lipogenic aptitude [ 13 ] and were preserved at − 80 °C in the Industrial Yeast Collection DBVPG of the Department of Agricultural, Food and Environmental Sciences, University of Perugia, Italy. Salient information on strains is reported on the DBVPG website ( http://www.dbvpg.unipg.it ).…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant strains of Yarrowia lipolytica have been extensively studied for obtaining high lipid productions [ 9 11 ]. However, some recent studies found that some basidiomycetous yeasts can be considered as possible alternatives to conventional oleaginous yeasts due to their high aptitude to accumulate lipids [ 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A triagem e seleção dos componentes do meio de cultivo são importantes para tornar o processo de produção economicamente viável, principalmente porque essa composição é específica para cada organismo produtor (GHOLAMIAN et al, 2013 (MAŠÍNOVÁ et al, 2017;FILIPPUCCI et al, 2016;WANG et al, 2015 (GUTIÉRREZ-ALONSO et al, 2009) e R.…”
Section: 3triagem E Seleção De Fatores Nutricionaisunclassified
“…que mostrou crescimento também em meio com xilose e maltose, mas não foi capaz de crescer em galactose e celobiose(FILIPPUCCI et al, 2016). Em outro estudo, L. muscorum foi capaz de assimilar sorbose, xilose, lactose e rafinose(LAICH et al, 2014).…”
unclassified